Leitfaden zum Datenschutz in medizinischen Forschungsprojekten Generische Lösungen der TMF 2.0 - Pommerening, Klaus (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2014)
The trust of patients and test subjects is an indispensable prerequisite for the success of medical research projects that cannot be carried out without the collection, long-term storage and analysis of clinical data and samples. Medical research today mainly works in networks in increasingly larger research networks. Accordingly, the importance of data protection and data security continues to increase. The TMF published generic data protection concepts for medical research associations in 2003 for the first time. On this basis, numerous research projects were able to develop and coordinate their data protection concepts more quickly. The experience gained has been incorporated into the fundamental revision of the generic concepts. The new concept of the complexity of medical research processes takes account of this with a modular structure and was also embedded in a comprehensive guideline.